THE ROLE OF POLITICAL PARTIES IN FORMING A RULE OF LAW AND CIVIL SOCIETY IN ENSURING THE DEVELOPMENT OF UZBEKISTAN - Bozorboyev Eldorbek Husniddin Uglii (Ecominds Press, 2025)
This article analyzes the role of political parties in the process of forming a rule of law and civil society in the Republic of Uzbekistan. Political parties, as political institutions of society, play an important role in state administration, contribute to the development of democratic principles and serve as an important factor in the formation of civil society. After Uzbekistan gained independence, the principle of multi-party system was introduced in the political system, and political parties have been actively participating in the process of determining state policy and implementing it. The article discusses the impact of political parties on the development of the country, their participation in the legislative and executive branches, their role in increasing the political activity of citizens, and their contribution to strengthening the principles of the rule of law.
Keywords: Political parties, rule of law, civil society, democracy, electoral process, legislation, public administration, political reforms, political institutions, civic activity.